A review: Data mining brainwave - Saibul @ Cyril, Patricia; Shibghatullah, Abdul Samad; Md Salleh, Norhaziah (2007)
Data mining has been long a topic of many international conferences. The term data mining has pressure many researchers to take part in discovering knowledge. Since data mining become an active research area, many tools have been introduced to the worldwide. However, in order to use such a data mining tool, we must ﬁrst understand the concepts of data mining, how data mining works and what techniques does it provides. Fundamentally, data mining is related with data, information and knowledge, which concerns on the process of ﬁnding relationships and discovering hidden patterns that exists in a large database. This paper presents the deﬁnition of data mining from many points of view and covers only six techniques that have common application in the real world situation. In addition, some of data mining application will be cover at the end of this paper.